Formulasi Edible Coating Berbasis Limbah Pertanian untuk Menjaga Kualitas Nanas - Maharsih, Inggit Kresna; Pusfitasari, Memik Dian; Ernawati, Lusi; Putri, Citra Ayu Saraswati; Hidayat, Muhammad Taufiq (Jurnal Keteknikan Pertanian, 2022)
Pineapple (Ananas comosus) is one of the leading fruit commodities in Indonesia. However, pineapple is very sensitive and easily deteriorate. An alternative to prevent the phenomenon is by using an edible coating on minimally processed pineapple. In this study, edible coating is made from cassava peels starch, chitosan, and glycerol. Chitosan cannot dissolve directly into water, hence it must be dissolved in variations of acids, namely citric acid and acetic acid. In addition, citric acid and acetic acid are antioxidant agents. The purpose of this study is to obtain the best edible coating composition to protect minimally processed pineapple from decaying. Edible coating is made by varying the concentrations of cassava peels starch, glycerol, and types of acids for dissolving chitosan. The best result was obtained as Variable M that contained 5% w/v of starch, 0.6 mL/gr of glycerol, 1% w/v of chitosan with addition of 2% w/v of citric acid. Browning occurred on day 14 when the pineapple coated with Variable M stored at 12.4oC with the percentage of vitamin C loss was 1.11%. These results were also in accordance with the sensory test data, that pineapples with Variable M coating obtained the highest average preference value for the parameters of aroma, texture, color, taste, and total acceptance.